Research advance of N 6-methyladenosine (m6A) in insect - ZHAO Shudi; WU Xiaofeng (浙江大学学报. 农业与生命科学版)
RNA modifications play vital roles in regulating gene expression of eukaryotes. The most prevalent RNA modification among them is N 6-methyladenosine (m6A), which is involved in a series of physiological activities. The mechanism of m6A regulatory enzymes as well as reader proteins, the process of m6A dynamic regulation, and the regular pattern of m6A distribution in mRNAs were introduced, and the typical biological functions of m6A mainly according to the recent progresses made in insects were summarized. Above the review, we preview the research and application prospects of m6A from the aspects of vacancies existing in current study and related phenomenon to be explain, aimed at forming the latest reference for exploration of m6A in insects.